2012
DOI: 10.1108/00400911211265639
|View full text |Cite
|
Sign up to set email alerts
|

Older and younger workers: the equalling effects of health

Abstract: Older and younger workers, the equalling effects of health Abstract Purpose:The paper considers the statistical evidence on the effects that ill health has on labour market participation and opportunities for younger and older workers in the East Midlands. Design/methodology/approach:A statistical analysis of LFS data was undertaken to demonstrate that health issues affect older and younger workers alike. This has an equalling effect on labour market opportunities, which should reduce any potential for interge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…McNair (2006) suggested that the labour market for older workers was distinct from the labour market for those younger than 50, highlighting that older workers were not always appreciated. In the current tight labour market characterised by the recession issues such as flexibility, skill shortages and health concerns have levelled the playing field between older and younger workers (Beck and Quinn, 2012). Overall, labour market data indicates that older workers are in a comparatively strong position in the current recession.…”
Section: Introductionmentioning
confidence: 99%
“…McNair (2006) suggested that the labour market for older workers was distinct from the labour market for those younger than 50, highlighting that older workers were not always appreciated. In the current tight labour market characterised by the recession issues such as flexibility, skill shortages and health concerns have levelled the playing field between older and younger workers (Beck and Quinn, 2012). Overall, labour market data indicates that older workers are in a comparatively strong position in the current recession.…”
Section: Introductionmentioning
confidence: 99%
“…Health conditions are often acquired with age, and we would expect older workers to be more at risk than the young workforce. This is broadly true, but nonetheless there are substantive levels of ill health among young people (Beck & Quinn, 2012;Levin, Walsh & McCartney, 2014). McLean et al (2014) found that socioeconomic inequality was associated with multimorbidity not just in older people, but from early adulthood onwards.…”
Section: Social Inequality and Healthmentioning
confidence: 98%
“…Friis, Wittchen, Pfister and Lieb (2002) identified family, education and work as key domains for the prevention of depression. Given the evidence that the health impacts of youth unemployment can be serious and enduring, it follows that work and learning for NEET young people must be of particular interest as a target for primary prevention (Allen, Hetrick, Simmons & Hickie, 2007;Beck & Quinn, 2012;Monroe & Harkness, 2005). For Patton et al (2016), NEET rates represent a headline indicator of adolescent health status.…”
Section: Neet Young People As a Target Group For Public Health Interv...mentioning
confidence: 99%